Cytochrome P450 and Glutathione S-Transferase Confer Metabolic Resistance to SYP-14288 and Multi-Drug Resistance in Rhizoctonia solani - Cheng, Xingkai; Dai, Tan; Hu, Zhihong; Cui, Tongshan; Wang, Weizhen; Han, Ping; Hu, Maolin; Hao, Jianjun; Liu, Pengfei; Liu, Xili (Frontiers in Microbiology, 2022)
SYP-14288 is a fungicide as an uncoupler of oxidative phosphorylation, which is effective in controlling fungal pathogens like Rhizoctonia solani. To determine whether R. solani can develop SYP-14288 resistance and possibly multi-drug resistance (MDR), SYP-14288-resistant mutant of R. solani X19-7 was generated from wild-type strain X19, and the mechanism of resistance was studied through metabolic and genetic assays. From metabolites of R. solani treated with SYP-14288, three compounds including M1, M2 and M3 were identified according to UPLC-MS/MS analysis and M1 accumulated faster than M2 and M3 in X19-7. When X19-7 was treated by glutathione-S-transferases (GST) inhibitor diethyl maleate (DEM) and SYP-14288 together, or by DEM plus one of tested fungicides that have different modes of action, a synergistic activity of resistance occurred, implying that GSTs promoted metabolic resistance against SYP-14288 and therefore lead to MDR. By comparing RNA sequences between X19-7 and X19, six cytochrome P450s (P450s) and two GST genes were selected as a target, which showed a higher expression in X19-7 than X19 both before and after the exposure to SYP-14288. Furthermore, heterologous expression of P450 and GST genes in yeast was conducted to confirm genes involved in metabolic resistance. In results, the P450 gene AG1IA_05136 and GST gene AG1IA_07383 were related to fungal resistance to multiple fungicides including SYP-14288, fluazinam, chlorothalonil and difenoconazole. It was the first report that metabolic resistance of R. solani to uncouplers was associated with P450 and GST genes.